SINTESIS DAN KARAKTERISTIK BATANG TANAMAN RUBIK (CALOTROPIS GIGANTEA) SEBAGAI MATRIKS PLASTIK BIODEGRADABLE - khairun nisah (Lantanida Journal, 2018)
Indonesian people consider the Rubik plant (Calotropis gigantean) is only a wild plants that have no benefits. It is often felled and thrown away. This study was aimed to provide the information the utilized these crops. This research was conducted to determine the ability and characteristics of Rubik stems (Calotropis gigantean) as an addictive substance plasticizer filler, where the rubrik plant was taken at the seaside area of Banda Aceh. Preparation of plasticizers from the filler of this rubric stem was used as an antiseptic and biodegradable plasticizer. The results of FT-IR spectra measurements of the filler plastics of this rubrik plant have a distinct tannin functional group absorption, at 923.850 cm-1 strong buckling numbers were indicated the presence of a potent buckling C-H group due to the presence of the aromatic groups in the tannin compound. For the SEM test, the plasticizer has a porous surface morphology of the outermost layer, this indicates the density of particles smaller than the plasticizer 2 grams of water compared to plasticizer 1 gram of water. The test of biodegradable and Aspergillus Niger fungi on time variations about 10 days were resulted in significant degradation. The rate of degradation with soil was greater than the Aspergillus Niger. Toxicity was used of Escherichia coli bacteria in medium of nutrient agar at 37Â°C with 48 hours incubation where in plasticizer has antiseptic to Escherichia coli.